The Effect of Customer Satisfaction on Financial Performance with Digital Service Systems as a Moderating Variable at PerumdaTirtanadi - Popy Wulandari; Renny Maisyarah; Rahima Br. Purba (International Journal of Economics and Management Sciences, 2025)
This research explores the influence of customer satisfaction on the financial performance of Perumda Tirtanadi, with a particular focus on the digital service system as a moderating factor. The study is driven by the growing urgency for digital innovation in public service sectors, particularly in the wake of the COVID-19 pandemic, which significantly altered customer engagement patterns. A quantitative method is adopted, employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) using the SmartPLS 4 software to process the collected data. The analysis demonstrates that both customer satisfaction and digital services have independent and significant positive effects on financial outcomes. However, the interaction between these two variables does not show a statistically significant moderating effect. These findings underline the value of digital infrastructure as a strategic internal resource that supports financial growth. Nevertheless, the minimal moderating impact suggests that a portion of customers either lack access or sufficient skills to effectively utilize the available digital platforms. This study adds to the current body of knowledge by examining the interplay between digital transformation and customer satisfaction in shaping financial performance, framed through the Resource-Based View (RBV) theory. The research suggests that improving digital literacy and promoting better adoption of digital tools among customers is essential to fully capitalize on the benefits of technological advancement. Furthermore, it highlights the need for continuous training and support to ensure that all customers can engage with digital services effectively, thereby enhancing overall satisfaction and financial performance. By addressing these gaps, organizations can foster a more inclusive digital environment that benefits both the customers and the service providers.